2006
DOI: 10.1523/jneurosci.1293-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Corticofugal Output from the Primary Somatosensory Cortex Selectively Modulates Innocuous and Noxious Inputs in the Rat Spinothalamic System

Abstract: Sensory maps for pain can be modified by deafferentation or injury, and such plasticity has been attributed mainly to changes in the convergence of projections in "bottom-up" mechanisms. We addressed the possible contribution of "top-down" mechanisms by investigating the functional significance of corticofugal influences from the primary somatosensory cortex (S1) to the ventroposterolateral thalamic nucleus (VPL). The strong convergence of spinal and lemniscal afferents to the VPL and the close correspondence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 55 publications
4
34
0
Order By: Relevance
“…A GABAergic hypofunction of this network followed by pain hypersensitivity and delayed loss of sensory neurons was proposed as an explanation for neuropathic pain [Canavero and Bonicalzi, 1998;DaSilva et al, 2008;Woolf and Salter, 2000]. Recent studies have shown under experimental conditions in rats that a decrease of glutamatergic excitatory or alternatively an increase of GABAergic inhibitory drive from SI would reduce thalamic responsiveness to painful stimulation [Monconduit et al, 2006;Wang et al, 2007]. Thus, the observed cortical signal reduction in the present study may reflect a top-down mechanism to reduce pain related relay.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…A GABAergic hypofunction of this network followed by pain hypersensitivity and delayed loss of sensory neurons was proposed as an explanation for neuropathic pain [Canavero and Bonicalzi, 1998;DaSilva et al, 2008;Woolf and Salter, 2000]. Recent studies have shown under experimental conditions in rats that a decrease of glutamatergic excitatory or alternatively an increase of GABAergic inhibitory drive from SI would reduce thalamic responsiveness to painful stimulation [Monconduit et al, 2006;Wang et al, 2007]. Thus, the observed cortical signal reduction in the present study may reflect a top-down mechanism to reduce pain related relay.…”
Section: Discussionsupporting
confidence: 54%
“…c, contralateral; i, ipsilateral. Levels of statistical significance: ***P < 0.0001, **P < 0.01, *P < 0.05. to tactile stimulation [Lamour et al, 1983;Monconduit et al, 2006]. Further, it was demonstrated that thalamocortical inputs following noxious stimulation are not clearly segregated into anatomically distinct regions in rats [Monconduit et al, 2006], and accordingly a less confined somatotopy for noxious compared to innocuous inputs has been observed in human somatosensory cortex [Apkarian et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, a five-channel Eckhorn mini-matrix microdrive system (Thomas Recordings) was used. Microelectrode signals were amplified, filtered, digitized, and discriminated with a personal computer-controlled multichannel neuronal acquisition processor (Plexon) as described previously (Monconduit et al, 2006). Baseline cortical activity and evoked trigeminovascular neuronal responses were obtained and analyzed as cumulative frequency and poststimulus histograms (PSTHs), respectively, to detect the occurrence of statistically significant neuronal responses.…”
Section: Methodsmentioning
confidence: 99%
“…Direct manipulation of the S1 cortex modulates the neuronal activity evoked by innocuous and noxious peripheral stimulation in downstream brain areas associated with pain signaling including the thalamus and anterior cingulate cortex (9,13). Such S1 cortex manipulation can temporarily relieve neuropathic pain in humans and animals (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%